2019
DOI: 10.1080/16089677.2019.1640490
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical relevance of thyroid autoantibodies in patients with goitre in Nigeria

Abstract: Background: Thyroid autoimmunity was thought to be rare in Africans but there is evidence that its prevalence is increasing. Since undetected autoimmune thyroid disease carries considerable morbidity, this study set out to determine the proportion of patients with goitre who have thyroid autoantibodies and the relationship, if any, between the presence of thyroid autoantibodies, thyroid function and thyroid size. Methods: The study was cross-sectional and conducted over a 12-month period. It involved 100 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In our study, the mean (SD) age at which hypothyroidism occurred was 40.70 ±14.31 years in the control group. These observations were consistent with earlier studies of thyroid disorders conducted by Ogbera et al in Lagos, Ojo et al 19 in Ile-Ife, Chehade et al 20 in the United States, and McGrogan et al 18 in Nigeria, who discovered a mean age of 40 ±12.4 years, 42.7± 12.6 years, 47.8± 14.9 years, and 44.6 ±13.8 years, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the mean (SD) age at which hypothyroidism occurred was 40.70 ±14.31 years in the control group. These observations were consistent with earlier studies of thyroid disorders conducted by Ogbera et al in Lagos, Ojo et al 19 in Ile-Ife, Chehade et al 20 in the United States, and McGrogan et al 18 in Nigeria, who discovered a mean age of 40 ±12.4 years, 42.7± 12.6 years, 47.8± 14.9 years, and 44.6 ±13.8 years, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to the results of a study that showed the presence of anti-TPO antibody in hypothyroidism was 100%, while hyperthyroidism was 76.3% and euthyroidism was 7%. (Ojo et al, 2019). Moreover, it was found that the highest percentage of patients with anti-TPO antibodies in the hypothyroidism group was 71.40%, which may indicate a higher risk of HT.…”
Section: A Distribution Of Patients According To the Type Of Thyroid ...mentioning
confidence: 90%
“…Graves' disease is becoming more prevalent in African areas, which are transitioning from iodine deficient to iodine sufficient. The prevalence of autoimmune hypothyroid disorders is low, compared to European or North American countries [8]. With the absence of laboratory testing, thyrotoxicosis should be suspected when there is a combination of thyroid enlargement (diffuse or nodular) and clinical signs of hyperthyroidism, such as loss of weight, tremor, sweating, anxiety, hyperactivity, palpitations, tachycardia or exophthalmos.…”
Section: Thyrotoxicosis and Auto-immune Disordersmentioning
confidence: 99%